Marketing Public Relations Event Iims Infinite Live 2024 Dalam Meningkatkan Brand Image Melalui Publikasi - Syifa Safitri Rukmindari,; Aan Setiadarma, (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The incident that occurred at IIMS Infinite Live 2023 due to heavy rain so that the closing band's performance was delayed for a long time and caused disappointment in the audience. From this disappointment, of course, increasing Brand Image is very influential. This research aims to analyze the Marketing Public Relations Strategy of the IIMS Infinite Live 2024 Event in building Brand Image through publications with a focus on the MPR Trilogy Strategy. This research uses descriptive qualitative research methods with a case study approach. Techniques used with in-depth interviews and documentation. The results of this study show that, Pull strategy focuses on media partner publications through social media and OOH in print and digital form. The Push strategy focuses on Media Gathering and Press Conference activities which are then published through press releases and through publication on IIMS Infinite Live Instagram as a form of interaction with followers. The Pass strategy focuses on carrying out good cooperation with external stakeholders through publications on Instagram social media and print IIMS Infinite Live 2024.